Italy : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that the economic slowdown in Italy in 2001 has been followed by only a modest resumption of growth in the first half of 2002. As weaker external demand spilled over into domestic demand, economic growth stagnated in the last three quarters of 2001. GDP growth turned marginally positive in the first half of 2002, although final domestic demand remained weak, as did industrial production, notwithstanding a rebound in business confidence from its 2001 trough. Equity prices have fallen by more than 20 percent from end-2001 to mid-October 2002.